Analysing concordancing: a simple or multifaceted construct?. Issue 7 (2nd October 2016) - Ballance, Oliver James
ABSTRACT: In pedagogical contexts, concordancing is often researched in relation to a non-concordanced-based learning condition, such as dictionary-based learning, and studies have generally shown concordancing to be a valuable language learning resource, as indicated by Tom Cobb and Alex Boutlon's recent meta-analysis. However, studies framed in terms of concordancing often overlook potentially significant differences in concordancing conditions by treating concordances as a simple, unidimensional construct. This study identifies variables within concordancing that may provide learners with diverging affordances, affordances that are not mutually compatible, and explores concordancing through a survey of concordance users' preferences. The data is analysed through a series of factor analyses which indicate that concordancing is a complex, multidimensional construct. It finds that there are at least four factors underlying the construct of concordancing: how citations are formatted, the type of corpus used, the order citations are presented in, and the task engaged in. Each of these factors represents a dimension of variance amongst concordance users. If it is safe to assume that concordance users' preferences are unlikely to be arbitrary, and are likely to indicate the affordances of concordancing in a particular configuration, then each factor represents a potentially significant variable in learner use of concordances. The paper concludes by discussing the implications of the construct identified in relation to learner concordance use.